The torso receptor localizes as well as transduces the spatial signal specifying terminal body pattern in Drosophila. - Casanova, J.; Struhl, G. (Nature, 1993)
Specification of the end portions of the Drosophila body depends on the torso (tor) protein, a receptor tyrosine kinase that accumulates uniformly along the entire surface of the embryo but is activated only in the vicinity of the poles. Several genes are normally required for activating tor and appear to define a system in which a gene product tethered to the extracellular vitelline membrane at each end of the egg provides a local source for an extracellular tor ligand. This ligand would have to diffuse from the membrane to the cell surface of the embryo without losing its spatial localization. Here we report that the failure to accumulate tor protein at one or both poles leads to spatially inappropriate activity of more centrally located receptor. This ectopic activity depends on the same gene functions normally required for activating tor; thus we infer that it reflects inappropriate diffusion of the ligand to more central regions of the body. We conclude that the receptor not only transduces the spatial signal imparted by the tor ligand, but also ensures its correct localization by sequestering the ligand. Ligand trapping by receptor may also localize spatial signals in other patterning systems, including specification of the dorsal-ventral axis in Drosophila and of vulval cell fates in Caenorhabditis elegans.